Fifteen-Year Follow-Up of a Case of Surgical Retreatment of a Single Gingival Recession - Luca Francetti; Silvio Taschieri; Nicolò Cavalli; Stefano Corbella (Case Reports in Dentistry)
Purpose. The aim of the present case report was to describe the retreatment of the single gingival recession in aesthetic area, in the presence of scar formation and consequent impairment of aesthetic appearance. Methods. A young patient with one single recession of 4 mm of 2.1 was treated with coronally advanced flap and subepithelial connective tissue graft, through a microsurgical approach that aimed at the removal of the scarred fibrous tissue. The intervention was performed using a surgical microscope as a magnification device. Results. Fifteen years after the surgical treatment, a substantial stable resolution of the gingival recession could be observed. Moreover, a further improvement of the aesthetic appearance could be observed. Conclusions. This case report suggests that periodontal microsurgery could be an effective approach for the retreatment of gingival recessions and, in long-term evaluation, to reduce the aesthetic problem due to the presence of scar formation. Further studies with a larger sample size are needed to better evaluate its efficacy.